2013
DOI: 10.1039/c2ta00406b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide–chitosan composite hydrogels as broad-spectrum adsorbents for water purification

Abstract: Water pollution is one of the most pervasive problems afflicting people throughout the world, while adsorption is the most widely used method to remove the contaminants from water. Here, in this paper, we report an eco-friendly graphene oxide-chitosan (GO-CS) hydrogel as a new type of adsorbent for water purification. The GO-CS hydrogels were prepared via self-assembly of GO sheets and CS chains. A three-dimensional network composed of GO sheets crosslinked by CS was found in GO-CS hydrogels.The GO-CS composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
325
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(335 citation statements)
references
References 58 publications
10
325
0
Order By: Relevance
“…The SEM image of NiNPs@rGO-bPEI aerogel (bPEI/ GO = 4) shows a plastic-like form (Fig. 4e, f) [59][60][61]. The TEM images of NiNPs@rGO-bPEI aerogel indicates the successful dispersion of Ni nanoparticles with the size of 18-20 nm on the surface of the rGO-based aerogel (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The SEM image of NiNPs@rGO-bPEI aerogel (bPEI/ GO = 4) shows a plastic-like form (Fig. 4e, f) [59][60][61]. The TEM images of NiNPs@rGO-bPEI aerogel indicates the successful dispersion of Ni nanoparticles with the size of 18-20 nm on the surface of the rGO-based aerogel (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Chitosan has been used with GO to prepare adsorbent hydrogel materials that have affinities for both cationic and anionic dyes, as well as heavy metals. The adsorption capacities of the dyes methylene blue and Eosin Y were reported as greater than 300 mg/g, while the adsorption of Cu(II) and Pb(II) were found to be 70 and 90 mg/g respectively [187]. A more complex material for the adsorption of Pb(II) has been realized by the combination of magnetic chitosan and GO that was imprinted with Pb(II) ions.…”
Section: Emerging Composite Graphene Materials For Enhanced Water Purmentioning
confidence: 99%
“…10 Chen et al studied the application of graphene oxidechitosan (GO-CS) composite hydrogels for the removal of organic dyes and found that the GO-CS composites showed maximal adsorption capacities towards cationic MB and anionic eosin Y with values of both being higher than 300 mg g À1 . 11 Recently, magnetic nanoparticle loaded adsorbent materials have been the subject of extensive attention because of their gentle operating conditions, easily manipulated process and high separation efficiency.…”
Section: 2mentioning
confidence: 99%